Low-cost and easy-to-use light spectroscopy can be used to monitor release behavior of essential oils - Maisurah, Syakirullah S.; Dandekar, Vikrant D.; Dhaliwal, Ishleen K.; Al-Gunaid, Hala T. (Narra Sains Indonesia, 2024)
Patchouli oil is considered a crucial ingredient for perfume, cosmetic, food and beverage manufacturing. Evaluating the volatility behavior of patchouli oil is important because it influences the aroma profile, quality, formulation, shelf life, therapeutic efficacy, and economic value of the oil. The aim of this study was to explore the ability of a low-cost and easy-to-use light-spectral triad sensor for the assessment of evaporation behavior of patchouli oil. We used a portable SparkFun Triad Spectroscopy Sensor comprised of three sensors including AS72651 (near-infrared range), AS72652 (visible range), and AS72653 (ultra-violet range). The sensor was connected to its Arduino-compatible microcontroller (SparkFun RedBoard) through Qwiic Connect System. The sensor's onboard microcontroller facilitated the collection of spectral data across 18 channels, encompassing wavelengths from 410 nm to 940 nm. The spectral data were observed qualitatively to determine the most optimum wavelength for analyzing the evaporation behavior. The data were modeled using autoregressive integrated moving average (ARIMA). Our findings revealed that the spectral intensity is distinguishable at λ=535 nm. The ARIMA modeling indicated that the crude essential oil follows an ARIMA (0,1,0) model with drift, characterized by a negative drift parameter of -1.35 (standard error (SE): 0.33; σ2=0.74). In contrast, the heavy fraction is best described by an ARIMA (0,0,0) model with a non-zero mean of 450.33 (SE: 0.35; σ2=0.86). Ljung-Box test suggested the absence of significant autocorrelation for both crude (p=0.33) and heavy fraction patchouli oil (p=0.5). In conclusion, the light spectroscopy is potential for monitoring the evaporation behavior of patchouli oil, though optimization remains necessary.